Relevansi Komunikasi Pembelajaran Dengan Materi Bahan Ajar SD/MI - Miptah Parid (Peneliti.net, 2020)
This article discusses the relevance of learning communication with SD / MI teaching materials. Communication that occurs in learning that there are educators who deliver learning material to students, students who discuss about certain topics that are included in the subject matter and so forth that involve interactions between educators, students or the environment. Learning material is a message in the learning communication process that is often considered to be the heart or core of learning activities. This research awaits research library reseach with a qualitative approach. The conclusion of this research is: learning communication is a process where educators build effective and affective communication relations with students so that students have the opportunity to achieve high effectiveness in the learning process. The characteristics of the learning communication process are: symbolic, dynamic, understandable, and unique. The types of communication carried out in learning communication are verbal communication and non verbal communication. Communication styles used in learning are aggressive, manipulative, passive, and assertive styles. Communication models that affect learning communication are laswel communication models and Schramme models